Analysis of Cyberbullying from a Pancasila Perspective - Wahyu Pujianto, Mario. B. Bagus; Astiti Putri, Ni Made Windi; Manurung, Evelyn Angelita Pinondang (Journal of Digital Law and Policy, 2024)
The rapid development in the field of technology has brought various positive and negative impacts. There are many typical crimes that occur, one of which is cyberbullying. These crimes take the form of oppression, insults, psychological violence or intimidation in cyberspace which is carried out repeatedly which is intended to embarrass, spread ugliness and hatred, intimidation which is directed directly or openly through digital devices and platforms such as social media, email, messaging applications, and gaming sites exist. Apart from that, there are several fundamental factors that form the background to the perpetrator's behavior and the impacts it causes. Cyberbullying cases are considered a violation of the 2nd and 5th principles of Pancasila. In responding to the problem of cyberbullying, Indonesia has sufficient laws and regulations to crack down on this criminal act of cyberbullying, one of which is Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE). By applying Pancasila values ??and understanding applicable laws, efforts to prevent and handle cyberbullying can be improved, creating a safer and more positive social media environment, especially for the nation's next generation. This research aims to determine the meaning, impact and ways to overcome it that are useful for provide knowledge to everyone. This research is research that uses a descriptive method in the type of literature study by describing, illustrating, explaining and analyzing the situation and conditions of the problem object from the researcher's perspective based on the results of the literature review.